(3eTGQjY eHJcQI hOQhS hJMOjGJ aj JQHjI hJfejI GdWahdI GdeHcQI (B: (3feGPL ef GdHdOGf GdYQHjI hGdYGdes - (3HjHj, ZGfes ((3HjQhJs (3GdjhfSchs, 2010)
(3jSdW gPG GdcJjH GdVhA Ydi GdeHGOQGJ GdEHJcGQjI GdfGLMI aj JWhjQ GdeYGQa ef Ohd GdYGde GdeNJdaI, hjecf GdeSDhdjf aj GdefWbI GdYQHjI GdESJaGOI efgG, GdHfGA YdjgG hGdJYde efgG(B. (3dYHJ GdeHGOQGJ GdNGUI OhQG CSGSjG aj EONGd GdeYQaI GdMOjKI hGdegGQGJ GdJj JYcS GdCgejI GdeYdfI dgPg GdeQMdI GdYeQjI, hNUhUG GdJYde GdeHcQ ajgG Ch eG jSei GdJQHjI bHd GdeOQSI(B. (3hbO TgO GdYbOGf GdCNjQGf WaQI aj EWdGb GdeHGOQGJ GdeHJcQI aj eNJda GdHdOGf GdYQHjI hGdYGde(B. (3eYXegG EYJeO Gdfbd Edi LGfH GdEHJcGQ hGdEHOGY aj GdhUhd Edi GdeYQaI hGdehGQO, hHYVgG CJjM dg Cf jKeQ hHYVgG Hbj ZjQ eYQha hYfGUQ GdEHJcGQ ajg HYjOI Yf Cf Jfbd hjYGO EfJGLgG(B. (3jJfGhd GdcJjH aUdjf feGPL ef gPg GdeTGQjY GdeHJcQI ef CLd JTGQcgG haJM GdfbGT Mhd OhQgG hecGfJgG(B: (3jMJhj GdaUd GdChd deMGJ Yf (B10 (3eHGOQGJ ef BSjG hTQb ChQhHG hCaQjbjG ENJjQJ ef Hjf CcKQ ef (B90 (3eTQhYG(B. (3cdgG LOjQI HCf JYee HGdYQHjI deG ajgG ef CacGQ LOjOI hOQhS hJMOjGJ hMdhd, hGdJLGQH GdYTQ GdeYQhVI JZWj LhGfH eNJdaI, LejYgG jecf GdJYde efgG(B. (3CeG GdaUd GdKGfj jMJhj Ydi (B19 (3eTQhYG ef HdOGf YQHjI eNJdaI, dG JOYj JeKjd cd GdLghO GdeHOYI hdG cd GdHdOGf, hdG gj fJjLI eSM fXGej ehSY, hdG Tc Cf aj GdHdOGf GdYQHjI YTQGJ ef GdfeGPL hGdESJQGJjLjGJ GdeVjFI GdJj jLH Cf jJGM dgG aQU GdJTGQc hGdJYde GdeJHGOd, hJbJUQ GdCSHGH GdJj MGdJ Ohf YQV GdcKjQ ef GdMGdGJ GdCNQi Ydi bUQ egdI GdEYOGO heMOhOjI GdbOQGJ GdeJGMI(B.s
(3GdfhY (B: (3cJGHs
Keywords: Arab Countries; Early Childhood; La petite enfance; Pays Arabes; (3GdOhd GdYQHjIs; (3GdWahdI GdeHcQIs